Identifying Physics Teachers Candidate Misconception on Electricity, Magnetism, and Solar System - Ruth Novi Kornalia Mellu; Doni T. Baok (STKIP Singkawang, 2020)
Misconception is a concept contradicts with scientific definitions or definitions approved by experts of particular field. Learners’ misconception cannot be eliminated but minimized so they do not grasp incorrect concept which can be identified through diagnostic tests. A research had been conducted to identify physics student teacher misconception. The research was undertaken using qualitative method with survey design. The population covered whole physics major students with 30 students of 6th semester as samples. Data collection was done by giving three tier multiple choice model of diagnostic test developed by Ambarwati on electricity, magnetism, and solar system materials. Data source of this study was primary data source since data was taken directly from research subjects. Data was analyzed using descriptive qualitative data analysis technique. The result showed that 18% students experienced misconception, 40% partially understood, 12% fully understood, and 30% did not understand concept. 20% misconception identification of electricity comprised static electric, determining physical quantity on circuit, defining electrical energy and power in daily life; 18 % magnetism material on how to make magnet or determining poles that affected electromagnetic induction; and 17% solar system material about characteristics of astronomical objects and emerging phenomena due to climate changing on earth surface. the identifications result implied a demand of developing and applying innovative, creative, and appealing learning in remediating and fixing misconception.